The Effect of Post Mortem Ageing and Muscle Type on Spent Hen Meat Quality : 10.5958/2581-6616.2020.00012.2 - M, Kiran; Kapase, Gangadhar; Kulkarni, Shrikant; kumar, Manoj; lakshmi, Vijaya (Journal of Meat Science, 2020)
Current investigation was carried out to study the changes in meat quality during ageing of thigh and breast muscles from spent hen meat at 4 °C. The pH of thigh muscle found to be higher (6.02) than breast muscle (5.78) throughout the ageing period. Water holding capacity increased (P
Keywords: 2-DE; Muscle fiber diameter; Myofibrillar fragmentation index; Proteolysis; Protein extractability